Theoretical and Empirical Study on Hardiness of Participants in Military Operations - Blikhar , Viacheslav; Kalka , Nataliya; Kuzo , Liubov (Insight: the psychological dimensions of society, 2024)
The aim of the article is to conduct a theoretical and empirical analysis of the distinctive characteristics of hardiness exhibited by individuals who have participated in military operations, elucidating its correlation with coping strategies. Methods. Psychodiagnostic techniques were used to achieve the aim: the Hardiness Scale by S. Maddi; the Stress and Coping Inventory (SCI) by R. Lazarus and S. Folkman. Statistical methods of data analysis (comparative and correlational analyses) were applied. The empirical study sample consisted of 35 men aged 22–55 who were in Ukraine and were involved in various ways in armed conflict (special operations forces, territorial defence, volunteers, etc.). Results. The indicators of the components of hardiness in the sample were distributed as follows: “engagement” characterized by a high level in 63.50% of respondents, a medium level in 28.30%, and a low level in 8.20%; “control” – a high level in 69.20%, a medium level in 15.30%, a low level in 15.50%; “risk acceptance” – a high level displayed only by 14.10%, a medium level by 35.30%, a low level by 50.60%. Dominant coping strategies among the subjects were found to be “acceptance of responsibility” (M = 15.10), “self-control” (M = 14.50), and “confrontational coping” (M = 10.30). The lowest level of coping was observed in “positive reappraisal” (M = 5.60). According to the results of the conducted correlational analysis, the following correlations were established: a correlation between “engagement” and “problem- solving planning” (R = .432; p ≤ .01) and “acceptance of responsibility” (R = .451; p ≤ .01), “risk acceptance” and “confrontational coping” (R = .611; p ≤ .01) and “escape-avoidance” coping (R = .550; p ≤ .01). As a result of the theoretical and empirical study, the characterization of personality hardiness in the context of stress resistance and vitality is presented. It was established that the key to the formation of hardiness is the development of personality vitality, which helps to overcome crisis situations. Hardiness is considered as a set of competencies enabling individuals not only to endure adversities but also to become stronger or acquire new skills. Discussion and conclusions. Empirical findings highlight the prevalence of hardiness components such as control and engagement among participants, contrasted with a notably lower inclination towards risk acceptance. Predominant coping strategies include “acceptance of responsibility”, “self-control”, and “confrontational coping”, while “positive reappraisal” coping exhibits the lowest manifestation. Correlations between coping strategies and hardiness components are delineated, namely: “engagement” correlating with “acceptance of responsibility” and “problem-solving planning”, and “risk acceptance” correlating with confrontational coping and “escape-avoidance” coping. These findings expand the directions of psychological support and aid available to individuals for cultivating hardiness and facilitating effective adaptation during crises situations.
Keywords: stress, hardiness, coping, coping strategies, crisis situation.